Investigation on photoluminescence quenching of CdSe/ZnS quantum dots by organic charge transporting materials - Yuqiu Qu (Materials Science-Poland, 2015)
The effect of different organic charge transporting materials on the photoluminescence of CdSe/ZnS core/shell quantum dots has been studied by means of steady-state and time-resolved photoluminescence spectroscopy. With an increase in concentration of the organic charge transporting material in the quantum dots solutions, the photoluminescence intensity of CdSe/ZnS quantum dots was quenched greatly and the fluorescence lifetime was shortened gradually. The quenching efficiency of CdSe/ZnS core/shell quantum dots decreased with increasing the oxidation potential of organic charge transporting materials. Based on the analysis, two pathways in the photoluminescence quenching process have been defined: static quenching and dynamic quenching. The dynamic quenching is correlated with hole transporting from quantum dots to the charge transporting materials.